A coding-independent function of an alternative Ube3a transcript during neuronal development - Valluy, Jeremy Matthias; Bicker, Silvia; Aksoy Aksel, Ayla; Lackinger, Martin; Sumer, Simon; Fiore, Roberto; Wüst, Tatjana; Seffer, Dominik; Metge, Franziska; Dieterich, Christoph; Wöhr, Markus; Schwarting, Rainer; et al. (Nature neuroscience, 2015)
This work shows a nocoding function of Ube3a1 RNA, an alternative transcript encoded by the Angelman syndrome gene Ube3a. Valluy et al. observe that Ube3a1 RNA competes with dendritic mRNAs for microRNAs, thereby regulating dendrite arborization and spine maturation of hippocampal neurons. These findings suggest a function for competing endogenous RNAs in synaptic development.